Socialization of Protection and Insurance Claim Processes for Drivers of Application-Based Companies in Palangka Raya, Indonesia - Wening Mustikaningsih; Nova Riyanti (Civitas : Jurnal Pengabdian Masyarakat, 2026)
This research study examines the digital transformation in Indonesia's urban transportation, which has increased the number of online drivers. However, this growth is decoupled from adequate insurance literacy. Adequate comprehension of social security is a prerequisite for professional safety. Initial findings in Palangka Raya indicate a critical baseline literacy score of 15.0, particularly with regard to Jasa Raharja's claim mechanisms. The present study evaluates a participatory educational intervention model with the objective of addressing this knowledge gap. Utilizing a pre-experimental design, the program encompassed ten drivers (N=10) from diverse platforms, including local’s "Parkur Delivery" drivers (n=3). The intervention's distinguishing characteristic is its participatory approach, integrating interactive discussions with hands-on claim form simulations. The effectiveness of the intervention was measured using instruments developed for the pre- and post-test, which were then analyzed through the Normalized Gain (N-Gain) test. The results indicated a substantial short-term improvement in participants' knowledge, with the overall average score increasing from 15.0 to 79.0 (N=10). Subsequent subgroup analysis for Parkur Delivery drivers (n = 3) demonstrated a consistent upward trend, aligning with the aggregate N-Gain value of 0.751 (high category). A singular finding emerged from the study: while procedural understanding exhibited an 80% improvement, legal-regulatory aspects remained the most challenging aspect for all participants. The simulation-based model appears promising for addressing procedural gaps, particularly within local delivery platforms. In the future, educational programs should prioritize the cultivation of legal literacy as a complement to practical skills. The study's limitations stem from its modest sample size (N=10), which necessitates additional replication to ascertain the study's generalizability across diverse demographics of platform users.